The Influence of Promotion and Influencers’ Credibility on Purchase Intention with Brand Image as a Mediation Variable (Study on Shopee Users among Students of Universitas Muhammadiyah Surakarta) - Sari, Rizki Iputa; Praswati, Aflit Nuryulia (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research aims to investigate the influence of promotional components and influencers’ credibility on the purchase intention of Shopee users among Universitas Muhammadiyah Surakarta students, with moderation from brand image. Influencer promotion and credibility are in focus due to their important role in influencing consumer behavior in the online environment. Apart from that, this research also aims to explore other possible variables that can influence purchase intentions, such as the influence of price and level of loyalty to e-commerce platforms. The method used was a survey using a questionnaire distributed to 150 Shopee user respondents, who were students at the Universitas Muhammadiyah Surakarta. The research results show that the promotion component and influencer credibility have a significant influence on Shopee users' purchasing intentions, which are moderated by perceived brand image. These findings emphasize the importance of effective promotional strategies and trust in influencers in forming positive perceptions of brands, which in turn influence consumer purchase intentions. However, these findings also underscore the importance of additional factors such as price and loyalty to e-commerce platforms in understanding online shopping behavior. Thus, this research implies the importance of further research on a broader scale to confirm and expand the findings revealed in this research.